О математическом моделировании трехмерного поля поперечных динамических смещений толстых упругих плит - Стоян, В.А.; Двирничук, К.В. (Кибернетика и системный анализ, 2013)
Досліджено динаміку пружної плити скінченних розмірів і товщини. Тривимірне поле поперечних динамічних зміщень плити будується як розв’язок двовимірних диференціальних рівнянь, параметрично залежних від поперечної координати. Розглянуто випадки дискретно- та неперервно-визначених початково-крайових умов, які задовольняються за середньоквадратичним критерієм. Описано особливості розв’язання поставлених задач в необмежених просторово-часових областях. We investigate the dynamics of an elastic plate of finite dimensions. The three-dimensional field of dynamic transverse displacements of the plate is constructed as a solution of two-dimensional differential equations parametrically dependent on the transverse coordinate. We consider the cases of discrete and continuous sets of the initial and boundary conditions that are satisfied by the mean square criterion. We describe the features of the solution of the problems in unbounded space–time domains. R